PENERAPAN ACTIVE CONTOUR MODEL PADA PENGOLAHAN CITRA UNTUK DETEKSI KERUSAKAN JALAN - Yuslena Sari; Andreyan Rizky Baskara; Puguh Budi Prakoso; Muhammad Arif Rahman (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
Road damage is a serious problem because it often occurs everywhere. Damage to the road surface, such as potholes, often disrupts land transportation, and can even cause accidents. With the automatic detection of road damage types, it can simplify the process of classifying the types of road damage by using images from the results of the classification system which can be used as supporting information in calculating road repairs. In this study, to identify road damage types by images, the active contour model segmentation technique is used based on the level set and then classified by the support vector machine method. Based on the test results, using 58 data sets with 12 types of road damage, the accuracy of this method is 87.93%.